Pemberian Edukasi Kesehatan Reproduksi Untuk Meningkatkan Pengetahuan Remaja di Universitas Wiraraja - Khalifah, Nurul; Sunartono, Sunartono; Dewi, Novita Puspita (Jurnal ABDIRAJA, 2025)
This community service aims to improve reproductive health knowledge among adolescents at Wiraraja University, Sumenep through a community approach. The focus of reproductive health education counseling includes how to care for reproductive organs, the impact of pornography exposure on adolescents, puberty criteria, and personal hygiene during menstruation. The community approach involves the Dean of Health Sciences who plays an active role in supporting the smooth running of this community service activity. This community service activity involved 25 Wiraraja University students as respondents who participated in an education program on reproductive health. Before the education was carried out, a pre-test was conducted to measure the respondents' basic knowledge, and after providing education, a post-test was conducted to measure the progress of their knowledge. The results of this community service showed a significant increase in knowledge among respondents. The respondents' knowledge score before providing education (pre-test) was 52.8, while after providing education (post-test) it increased to 78.4. The increase in score shows that providing reproductive health education through a community approach is very effective in increasing adolescent knowledge about the importance of reproductive health care, the negative impacts of pornography exposure, understanding of puberty, and maintaining personal hygiene during menstruation. These results prove that this community service program has a positive impact and can be a model in efforts to increase awareness of reproductive health among adolescents at the university level.